Context and Erection of Legal System in Ghana - Gedzi, Victor Selorme (Advances in Social Sciences Research Journal, 2015)
The paper has analyzed the erection of the formal legal system in Ghana. The research based its analysis on relevant textual and field materials, including observation. The finding has shown that socio-economic context of the colonial period has frame-worked the legal system Ghana inherited from the British. For example, the British have seen the courts as the appropriate way of dealing with cases associated with trade and resentment of local people at the sharp deals of their merchants. The erection of the legal system helped the British assume a broader and more lasting political control in the trading posts to defend and protect their merchants. Today, Ghana faces new challenges. To overcome them, Ghana needs to erect and enforce new laws that are contextually relevant to meet and direct the ongoing socio-economic processes. It means a restructuring and reforming the entire inherited colonial legal system. The study is important because, among other things, it has highlighted the context of the British colonial era which frame-worked the formal legal system in Ghana which needs contextualization to meet present realities for a more desirable micro and macro socio-economic transformation.